An analytical study of new material test method for tension under bending and compression in double side incremental forming. (2017) - Ai, Sheng; Lu, Bin; Long, Hui
Abstract: Incremental sheet forming (ISF) has attracted considerable research interests owing to its unique advantages. Double side incremental forming (DSIF) was proposed to further improve the forming accuracy and material formability. Compared with conventional sheet forming technologies, ISF provides greater process flexibility and achieves an enhanced formability. At the same time, however, ISF has exhibited a far more complicated material deformation behavior for formability enhancement. It is now widely acknowledged that the material deformation during ISF consists of stretching, bending, and shearing with cyclic effects. Continuous bending under tension (CBT) testing method was proposed by Emmens et al. [1], which proved the cyclic stretch-bending effect for formability enhancement in single point incremental forming (SPIF). However, limited research had been reported to investigate the material deformation mechanism leading to the formability improvement in DSIF. An analytical model of a new material test method, Tension Under Bending and Compression (TUBC), is proposed in this study to investigate the material deformation leading to the formability enhancement in DSIF. Under TUBC condition, a specimen is stretched by the pulling force on both ends, while multiple rollers, in contact with the strip on both sides, move backward and forward continuously to create both cyclic bending and compression loading at a localized area. The analytical model is used to investigate the maximum stable elongations under TUBC condition. Key test variables, bending depth and compressive force, imposed by the rollers, are introduced to consider the effects of continuous bending, compression, and contact between rollers and workpiece. From the results obtained, it is clear that bending and compression have determinant effects on the formability enhancement of DSIF. However, the results show varied degrees of sensitivity of formability to different test variables. The findings correlate well with experimental observations and help to explain the formability enhancement of DSIF.